Odnos zdravstvenih delavcev do terminalnih bolnikov in njihove oskrbe - Russi Zagožen, Ingrid (Obzornik zdravstvene nege, 1998)
The article presents the results of a research, the first part of which investigated the attitude of medical personnel toward terminal patients and their care. The second part of the research explored the medical personnel's reactions of distress, discomfort and panic when confronted with a terminal pateint or his/her death. A questionnaire was administrated to 360 medical workers who participated in one of the Slovene Hospice Society seminars. In contacts with termial patients, 77.0% of medical personnel experienced the need to withdraw, 99.8% were deeply touched and frustrated at the moment o, and 29.1% were in panic. There is no uniform opinion and practices towards thecare of the terminal patient, but 79.0% consider their education insufficient, and most of them express the need for professional and patient'srelatives support.
Keywords: death; doživljanje smrti; nega bolnika; smrt; terminalni bolnik; umiranje; zdravstveni delavci